2000
DOI: 10.1614/0890-037x(2000)014[0100:sdiats]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sulfentrazone Dissipation in a Tennessee Soil1

Abstract: Sulfentrazone dissipation in soil was examined in field experiments in 1995, 1996, and 1997 at Knoxville, TN, on a Sequatchie loam soil. Sulfentrazone 50% disappearance time (DT50) varied from 24 to 113 d. Cotton injury was observed the year following sulfentrazone application when half-lives were ≥85 d. Sulfentrazone degradation under controlled laboratory conditions was slower in autoclaved soil than in nonautoclaved surface soil and subsurface soil, with DT50 of 198, 93, and 102 d, respectively. The differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 12 publications
1
60
1
10
Order By: Relevance
“…Thus HMS was shown to be one of the components in the metabolic degradation route of this herbicide by microorganisms in soil. Ohmes et al (25) showed that microbial degradation is an important mechanism for sulfentrazone dissipation, since its degradation was very low in autoclaved soils.…”
Section: Discussionmentioning
confidence: 99%
“…Thus HMS was shown to be one of the components in the metabolic degradation route of this herbicide by microorganisms in soil. Ohmes et al (25) showed that microbial degradation is an important mechanism for sulfentrazone dissipation, since its degradation was very low in autoclaved soils.…”
Section: Discussionmentioning
confidence: 99%
“…Uma possível explicação para essa tendência de maior degradação em condição de maior umidade pode estar relacionada ao fato da umidade ter uma influência direta sobre a proliferação dos micro-organismos degradadores e suas atividades (Martinez et al, 2008). A degradação microbiana é um mecanismo importante na degradação do sulfentrazone no solo uma vez que Ohmes et al (2000) observaram que a degradação foi muito lenta em solos autoclavados.…”
Section: Methodsunclassified
“…Ohmes et al (2000) observaram, avaliando a degradação do sulfentrazone nessa mesma temperatura, semelhantemente, uma degradação mais rápida do sulfentrazone (93 dias) em solo de superfície (profundidade de 0-10 cm) quando comparada à degradação observada (102 dias) em solo de subsuperfície (profundidade de 30-40 cm).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Sulfentrazone is a weak acid with a pKa of 6.56; therefore, it exists predominantly in ionized form in soils with a pH higher than the pKa (Senseman 2007). Sulfentrazone is relatively persistent in soil, with a half-life reported in the range of 24 to 302 days (FMC Corporation 1999;Martinez et al 2008;Ohmes et al 2000). Because of slow sulfentrazone dissipation in some soils especially under conditions of drought and cool weather, a potential risk of carry-over to rotational crops is of concern.…”
Section: Introductionmentioning
confidence: 99%